DETERMINATION OF PAHS IN UNDERGROUND WATER USING GC-MS AND GC-FID IN OSUN STATE, SOUTHWEST NIGERIA (FUDMA JOURNAL OF SCIENCES, 2025)
Contamination of underground water by polycyclic aromatic hydrocarbons (PAHs) poses significant health risks, yet the effectiveness of different analytical methods in detecting these contaminants remains unclear. This study compares the sensitivity of Gas Chromatography-Mass Spectrometry (GC-MS) and Gas Chromatography-Flame Ionization Detection (GC-FID) in analyzing PAH concentrations in borehole and well water in Osun State, Nigeria. Results showed that GC-MS detected a broader range of PAHs (22 compounds) compared to GC-FID (13 compounds), highlighting its higher sensitivity. While GC-FID recorded higher PAH concentrations in borehole samples, GC-MS provided a more precise differentiation of compounds. These findings emphasize the importance of selecting an appropriate detection method to accurately assess PAH contamination in drinking water, which is crucial for environmental monitoring and public health safety.
Keywords: GC-MS; GC-FID; Polycyclic aromatic hydrocarbons; Underground water contamination; Water quality assessment